2021
DOI: 10.3390/f12111599
|View full text |Cite
|
Sign up to set email alerts
|

Dead or Alive: Drivers of Wind Mortality Initiate Multiple Disturbance Regime in a Temperate Primeval Mountain Forest

Abstract: The driving forces of tree mortality following wind disturbances of mountain mixed European temperate forests belongs among issues not comprehensively resolved. Hence, we aimed to elucidate the key factors of tree resistance to historical severe disturbance events in the Boubínský Primeval Forest, one of the oldest forest reserves in the Czech Republic. By using spatially explicit tree census, dendrochronological and soil data, we study spatial and temporal patterns of past disturbances and mathematically comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…By shifting resources from growth towards production of secondary metabolites, “slow‐growers” gain selective advantage over “fast‐growers” by improving their defenses against environmental stressors and increasing wood resistance, but at the cost of reduced growth (Wiley & Helliker, 2012). On the other hand, “fast‐growers” get larger sooner, but rarely reach the same age as “slow‐growers,” as the initial advantage of dominant canopy position (i.e., increased light availability) and fast growth are offset by generally declining growth rates, decreased resilience to pests and pathogens, and reduced investments in defenses and biomechanical stability (Vašíčková et al, 2021). However, trees with more than half of a lifetime with suppressed growth seldom reach an age above 300 years (Figure 4), as continuous growth suppression and limited resources increase mortality risks (Munné‐Bosch, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…By shifting resources from growth towards production of secondary metabolites, “slow‐growers” gain selective advantage over “fast‐growers” by improving their defenses against environmental stressors and increasing wood resistance, but at the cost of reduced growth (Wiley & Helliker, 2012). On the other hand, “fast‐growers” get larger sooner, but rarely reach the same age as “slow‐growers,” as the initial advantage of dominant canopy position (i.e., increased light availability) and fast growth are offset by generally declining growth rates, decreased resilience to pests and pathogens, and reduced investments in defenses and biomechanical stability (Vašíčková et al, 2021). However, trees with more than half of a lifetime with suppressed growth seldom reach an age above 300 years (Figure 4), as continuous growth suppression and limited resources increase mortality risks (Munné‐Bosch, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pest infestation and wildfire do not necessarily occur after wind disturbance, even if weather conditions favor such events (Szwagrzyk et al, 2017). Soil conditions (e.g., periodically waterlogged or hydromorphic soils) also add to the variation in mortality (Mitchell, 1995;Vašíčková et al, 2021).…”
Section: Vulnerability After Partially Stand-replacing Disturbancesmentioning
confidence: 99%
“…At the same time, for trees with broken stems the mortality probability increased to 0.84 and uprooted trees had only marginal chances (mortality probability 0.98) to survive throughout the study period. Interestingly, Vašíčková et al (2021) noticed that storm Herwart (2017) selectively impacted the conifer population in the Czech Republic. They found that trees that germinated under the canopy and experienced several periods of suppression and release were more likely to survive the storm.…”
Section: Vulnerability After Partially Stand-replacing Disturbancesmentioning
confidence: 99%